O discurso publicitário midiático da Itaipava : as cenografias, a mulher e a cerveja em consumo - Marinho, Joyce Leite (2017)
Lately we have noticed in the media the constant and explicit presence of appealing discursive strategies and the exploration of the sensuality of women in the advertising campaigns of different brands of beer. The research on beer advertising is recurrent, but Itaipava beer gained market visibility in 2015 and, therefore, research with this corpus is recent. Our research aims to examine the role of interdiscourses, scenographies, the role of verbal-visual mechanisms, and the image of women as objects of consumption, in advertising speeches of Itaipava beer. To base the research, we use Discourse Analysis in its enunciative-discursive perspective, according to Dominique Maingueneau (2008a, 2008b, 2010, 2013, 2015), favoring the categories of interdiscourse, discourse genre and enunciation scenes. For Maingueneau, the advertising discourse does not present a fixed set design, is organized according to the interdiscursivity and is marked by a mediatic enunciation that is organized by verbal and nonverbal practices. The corpus of the research is divided into three groups, each composed of seven media discourses of Itaipava beer. These speeches are justified not only by their internal organization, but also by the way they appeal to the season, the summer, personalized in the model. The analysis revealed to us a speech marked by sensualism and an image of enunciator, concerned with highlighting the body and sensuality of women, while at the same time, through discursive strategies and with different scenographies, it produces manipulative meaning effects, in order to boost the consumption of the drink and the woman.